Scheduling design of Jakarta-Cikampek II elevated toll road project (P.186 – P.187) - Abdul Khalim; Harun Usman Ghifarsyam; Nikko Rozy; Faqih Ma’arif (Journal of Engineering and Applied Technology, 2020)
The key to achieving effective and efficient development goals is by increasing the quality of construction management by collecting up-to-date data about the project's resources, mainly about productivity. In this research space, productivity will be discussed, including human resources and their management. The case study is the project of Jakarta-Cikampek II Elevated Toll Road. This project was a developing project to improve the capacity of the existing Jakarta-Cikampek toll road. This elevated structure will be built right in the area (median and side edge) of the existing toll road, making it interesting to discuss how the construction is carried out. Scheduling analysis in this study was carried out at points P.186 to P.187 of the construction project. The analysis includes identifying the productivity index of labor resources and equipment that has a major role in shaping the scheduling concept. The concept will be performed by determining a network diagram that will use the Critical Path Method (CPM) rule. The data used in this analysis are construction drawing, s-curve plan, worker data, weekly job plan, work method, and some interviews with worker and field project manager. These results obtained the large productivity of workers and equipment, and the duration required to complete the construction starting prom point P.186 to P.187 is 248 working days